Capturing CO2 from ambient air using a polyethyleneimine–silica adsorbent in fluidized beds - Zhang, Wenbin; Liu, Hao; Sun, Chenggong; Drage, Trevor C.; Snape, Colin E. (Elsevier, 2014)
Carbon Capture and Storage (CCS) uses a combination of technologies to capture, transport and store carbon dioxide (CO2) emissions from large point sources such as coal or natural gas-fired power plants. Capturing CO2 from ambient air has been considered as a carbon-negative technology to mitigate anthropogenic CO2 emissions in the air. The performance of a mesoporous silica-supported polyethyleneimine (PEI)–silica adsorbent for CO2 capture from ambient air has been evaluated in a laboratory-scale Bubbling Fluidized Bed (BFB) reactor. The air capture tests lasted for between 4 and 14 days using 1 kg of the PEI–silica adsorbent in the BFB reactor. Despite the low CO2 concentration in ambient air, nearly 100% CO2 capture efficiency has been achieved with a relatively short gas–solid contact time of 7.5 s. The equilibrium CO2 adsorption capacity for air capture was found to be as high as 7.3 wt%, which is amongst the highest values reported to date. A conceptual design is completed to evaluate the technological and economic feasibility of using PEI–silica adsorbent to capture CO2 from ambient air at a large scale of capturing 1 Mt-CO2 per year. The proposed novel “PEI-CFB air capture system” mainly comprises a Circulating Fluidized Bed (CFB) adsorber and a BFB desorber with a CO2 capture capacity of 40 t-CO2/day. Large pressure drop is required to drive the air through the CFB adsorber and also to suspend and circulate the solid adsorbents within the loop, resulting in higher electricity demand than other reported air capture systems. However, the Temperature Swing Adsorption (TSA) technology adopted for the regeneration strategy in the separate BFB desorber has resulted in much smaller thermal energy requirement. The total energy required is 6.6 GJ/t-CO2 which is comparable to other reference air capture systems. By projecting a future scenario where decarbonization of large point energy sources has been largely implemented by integration of CCS technologies, the operating cost under this scenario is estimated to be $108/t-CO2 captured and $152/t-CO2 avoided with an avoided fraction of 0.71. Further research on the proposed 40 t-CO2/day ‘PEI-CFB Air Capture System’ is still needed which should include the evaluation of the capital costs and the experimental investigation of air capture using a laboratory-scale CFB system with the PEI–silica adsorbent.